Institutions, size and age in transition economies: Implications for export growth - Shinkle, George A; Kriauciunas, Aldas P (Journal of International Business Studies, 2010)
We consider the influence of economic institutions on firm performance by examining how size and age are related to export growth under different levels of free-market institutional development. Using a multi-country sample of Central and Eastern European firms, we test our predictions that size and age will have a positive diminishing relationship with export growth in transitional economies, but a U-shaped relationship in less advanced transitional economies. We find significant relationships largely in line with our predictions, demonstrating the importance of considering both economic institutions and firm characteristics when examining export growth.